Morphology and variation of the diatom Aulacodiscus margaritaceaus (Bacillariophyta) - Hernandez-Becerril, David U.; Pasten Miranda, Norberto (Instituto de Ecología, A.C., 1994)
Numerous specimens of the diatom Aulacodiscus margaritaceus Ralfs were found in the stomach contents of Atherinid fishes from the Gulf of California. This species was studied by light and scanning electron microscopy. The general morphology is consistent with earlier descriptions: the valve presents fairly coarse, loculate areolae closed by cribra on the outside and open to the inside by large foramina. However, externally the valve shows rather large granules lying on the porose cribra. Their density is variable, but in larger specimens the granules are densely distributed. There are tubular, external processes near the margin of the valve. The number of these processes may vary from 4 to 6 (4 to 10 in specimens of the type material), and it is common to find them broken. The processes end internally in horse-shoe shaped slits. On the internal valve surface hyaline rays sometimes run from the valve center to the rimoportulae. Comments are provided on the variability of this species, as well as on the origin of the external large granules.